The Education’s Philosophy and Logical Curriculum in University of Viet Nam - Hieu, Tran Minh (Journal for Developing the Social and Community, 2019)
Logic is taught in all colleges and universities in Vietnam with duration of 2 - 4 credits, depending on the discipline. In the academic year 2016-2017, Vietnam has 1,767,879 undergraduate students and 47,800 college students (Ministry of Education and Training. 2017). That means, every year, there are about 600,000 students studying the Logic. A number is impressive. Therefore the influence of the logic in student knowledge is significant. But the first thing to do when designing a curriculum is to define its goal. This goal is determined by the educational philosophy. In this paper, we discuss the influence of the educational philosophy on the development of the logic curriculum. We introduce the main contents of logical curriculum, the influence of educational philosophy on the design of the subject, and the difficulties of students when they study this subject. Finally, we recommend solutions to better teach logic.